2003
DOI: 10.1001/jama.290.7.932
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Risk Factors for Atherosclerotic Vascular Disease

Abstract: Context Atherosclerotic vascular disease is an enormous public health problem. A number of emerging risk factors for atherosclerosis have recently been proposed to help identify high-risk individuals.Objective To review the epidemiological, basic science, and clinical trial evidence concerning 4 emerging risk factors: C-reactive protein, lipoprotein(a), fibrinogen, and homocysteine.Data Sources Using the terms atherosclerosis, cardiovascular disease, risk factors, prevention, screening, C-reactive protein, lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
300
3
25

Year Published

2005
2005
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(334 citation statements)
references
References 124 publications
6
300
3
25
Order By: Relevance
“…(13,15) Another problem with reporting ASVD is that it consists of several categories, including coronary heart disease, cerebrovascular disease, and peripheral arterial disease. (16) These broad categories of atherosclerotic vascular disease are further broken down into subcategories of disease by the ICD coding system. Given the relatively low frequency of events in these subcategories of disease, it is possible to find statistical differences between groups owing to the problem of multiple statistical testing.…”
Section: Discussionmentioning
confidence: 99%
“…(13,15) Another problem with reporting ASVD is that it consists of several categories, including coronary heart disease, cerebrovascular disease, and peripheral arterial disease. (16) These broad categories of atherosclerotic vascular disease are further broken down into subcategories of disease by the ICD coding system. Given the relatively low frequency of events in these subcategories of disease, it is possible to find statistical differences between groups owing to the problem of multiple statistical testing.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, studies in primarily white-American populations suggest that inflammatory markers such as CRP levels have shown to independently predict cardiovascular disease and adverse cardiovascular outcomes (14)(15)(16)(17). Although the magnitude of the predictive contribution of inflammation beyond that of traditional cardiovascular risk factors is being debated (32,33), one of the mechanisms by which obesity and adiposity confer cardiovascular risk is likely through heightened inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen is an acute phase reactant that is increased in inflammatory states (24). Hepatic synthesis of fibrinogen can increase up to 4-fold in response to inflammatory or infectious triggers (25). Some earlier studies have identified fibrinogen as a major independent risk factor for cardiovascular diseases (26,27).…”
Section: Discussionmentioning
confidence: 99%